71.7k views
0 votes
Solve the equation (linear equation)


4^(x-7) ×
8^(2x-3) =(32)/(2^(x-9) )

User Karmakaze
by
5.6k points

2 Answers

1 vote

Answer:


x=4(1)/(9)

Explanation:

We are given the following linear equation and we are to solve it:


4 ^ { x - 7 } * 8 ^ { 2x - 3 } = \frac { 32 } { x ^ { x - 8 } }

Changing the constants to the same base to make it easier to solve:


2 ^ { 2 ( x - 7 ) } * 2^ { 3 ( 2x - 3 ) } = \frac { 2 ^ 5 } { 2 ^ { x - 9 } }


2^(2x-14) * 2^(6x-9) = 2^(5)(2^(-x+9))


2 ^ { 2x - 14 + 6x - 9 } = 2 ^ { 5 - x + 9 }


2 x + 6x - 14 - 9 = 5 - x + 9


8x+x=14+9+5+9


9x=37


x=4(1)/(9)

User Lebobbi
by
5.3k points
6 votes

Answer:
x=(37)/(9)

Explanation:

By the negative exponent rule, you have that:


((1)/(a))^n=a^(-n)

By the exponents properties, you know that:


(m^n)^l=m^((nl))


(m^n)(m^l)=m^((n+l))

Rewrite 4, 8 and 32 as following:

4=2²

8=2³

32=2⁵

Rewrite the expression:


(2^2)^((x-7))*(2^3)^((2x-3))=(32)/(2^((x-9)))

Keeping on mind the exponents properties, you have:


(2)^(2(x-7))*(2)^(3(2x-3))=32(2^(-(x-9))


(2)^(2(x-7))*(2)^(3(2x-3))=(2^5)(2^(-(x-9)))\\\\(2)^((2x-14))*(2)^((6x-9))=(2^5)(2^((-x+9)))\\\\2^(((2x-14)+(6x-9)))=2^((5+(-x+9)))

As the bases are equal, then:


(2x-14)+(6x-9)=5+(-x+9)\\\\2x-14+6x-9=5-x+9\\\\8x-23=14-x\\9x=37


x=(37)/(9)

User Tabarek Ghassan
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.